Пізні скіфи: формування складу населення за матеріалами антропології - Рудич, Т.О. (Археологія і давня історія України, 2020)
У статті на матеріалах краніології розглядається питання про формування пізньоскіфських
популяцій та їх місце в колі хронологічно близьких груп Східної Європи. In this paper, craniological materials from late
Scythian monuments were considered in a wide range
of Scythian, Sarmatian groups and series from ancient
necropolises. Statistical analysis was performed using
several methods of multidimensional statistics. According
to the results of the analysis it can be said that the
population from the Lower Dnieper settlements and
the Late Scythian cemeteries of Crimea is the common
anthropological massif which is biologically connected
with people from the ancient environment and people
from certain Scythian populations.
Due to its mixed population, Mykolayivka-Kozatsky,
Zolota Balka, Scythian Neapolis and Belyaus occupy
an intermediate position between groups from
Greek polises and individual Scythian series. From the
Scythian series to the late Scythians morphologically
and statistically the closest people from the cemetery
of Ak-Tash and Mykolayivka on the Dniester who
were in contact with the ancient world. Late Scythian
groups differ from the main Scythian population in a
number of ways. They have a smaller skull in length
and height, below the face and nose, but higher orbits,
as well as a sharper horizontal profile of the face. The
direction of the differences shows that they should not
be associated with epoch-making variability. The set
of features in the direction of which the late Scythian
population differs from the Scythians, is characteristic
of the population of ancient cities. People from these
cities were one of the two main components among the
late Scythian population. The Sarmatians did not play
a significant role in shaping the composition of the late
Scythian populations, but their presence among the
population is fixed.
Part of the descendants of the Late Scythian population
took part in the formation of the anthropological
composition of the bearers of Chernyakhiv culture.
This is recorded in materials from Chernyakhiv cemeteries
on the Black Sea coast. Some groups of people
from the late Scythian populations were buried in the
Chernyakhiv cemetery in the Middle Dnieper.